Robot-assisted Nissen fundoplication with the new Cambridge medical robotics-robotic assisted system - Prakash, Ved; Agrawal, Anirudh; Faraz, Mirza; Bhugra , Hemanshu (International Surgery Journal, 2025)
Over the last decade, robotic surgery has become increasingly prominent as a minimally invasive approach, with numerous studies validating its safety and clinical utility. This case report outlines a robotic-assisted nissen fundoplication procedure for hiatal hernia utilizing the CMR™ versius system. One of the distinguishing features of the system is its open console paired with a high-definition 3d display, along with lightweight robotic arms configured as four independent units. The procedure was completed successfully without requiring conversion to open surgery. No intraoperative complications or technical issues occurred. The surgical duration was approximately 150 minutes, with docking taking around 10 minutes. The patient’s hospital stays lasted three days. This case highlights the clinical utility, enhanced dexterity and technical feasibility of using the cmr™ versius system for performing Nissen fundoplication. The report also provides preliminary data that may help assess the benefits and limitations of this robotic platform in similar general surgical procedures.